Neuroimmune crosstalk in the cornea: The role of immune cells in corneal nerve maintenance during homeostasis and inflammation. (November 2022) - Wu, Mengliang; Hill, Lisa J.; Downie, Laura E.; Chinnery, Holly R.
Abstract: In the cornea, resident immune cells are in close proximity to sensory nerves, consistent with their important roles in the maintenance of nerves in both homeostasis and inflammation. Using in vivo confocal microscopy in humans, and ex vivo immunostaining and fluorescent reporter mice to visualize corneal sensory nerves and immune cells, remarkable progress has been made to advance our understanding of the physical and functional interactions between corneal nerves and immune cells. In this review, we summarize and discuss recent studies relating to corneal immune cells and sensory nerves, and their interactions in health and disease. In particular, we consider how disrupted corneal nerve axons can induce immune cell activity, including in dendritic cells, macrophages and other infiltrating cells, directly and/or indirectly by releasing neuropeptides such as substance P and calcitonin gene-related peptide. We summarize growing evidence that the role of corneal intraepithelial immune cells is likely different in corneal wound healing versus other inflammatory-dominated conditions. The role of different types of macrophages is also discussed, including how stromal macrophages with anti-inflammatory phenotypes communicate with corneal nerves to provide neuroprotection, while macrophages with pro-inflammatory phenotypes, along with other infiltrating cells including neutrophils and CD4 + T cells, can be inhibitory to corneal re-innervation. Finally, this review considers the bidirectional interactions between corneal immune cells and corneal nerves, and how leveraging this interaction could represent a potential therapeutic approach for corneal neuropathy. Highlights: Corneal sensory nerve impairment occurs in many ocular and systemic conditions. Corneal intraepithelial dendritic cells directly and indirectly interact with corneal sensory nerves. Corneal anti-inflammatory macrophages are beneficial to corneal nerve regeneration. Neuroimmune interactions can be targeted to develop immune cell-based therapeutic strategies to treat corneal neuropathy.